Упрощённое - 5+b, итог: 8 3/4
Объяснение:
-13,24+b+4,9+8,24+(-4,9), если b = 3 3/4
-13,24+b+4,9+8,24+(-4,9) = (-13,24+8,24)+(4,9-4,9)+b - используем правило от перемены мест слагаемых сумма не меняется.
(-13,24+8,24)+(4,9-4,9)+b = 5 + 0 + b = 5+b - вычисляем.
Подставляем:
5+b = 5 + 3 3/4 = 8 3/4 - итог
Упрощённое - 5+b, итог: 8 3/4
Объяснение:
-13,24+b+4,9+8,24+(-4,9), если b = 3 3/4
-13,24+b+4,9+8,24+(-4,9) = (-13,24+8,24)+(4,9-4,9)+b - используем правило от перемены мест слагаемых сумма не меняется.
(-13,24+8,24)+(4,9-4,9)+b = 5 + 0 + b = 5+b - вычисляем.
Подставляем:
5+b = 5 + 3 3/4 = 8 3/4 - итог